Media, messages, and medication: strategies to reconcile what patients hear, what they want, and what they need from medications - Kravitz, Richard L (BioMed Central, 2013)
BACKGROUND: Over the past 30 years, patients’ options for accessing information about prescription drugs have expanded dramatically. In this narrative review, we address four questions: (1) What information sources are patients exposed to, and are they paying attention? (2) Is the information they hear credible and accurate? (3) When patients ask for a prescription, what do they really want and need? Finally, (4) How can physicians reconcile what patients hear, want, and need? ANALYSIS: A critical synthesis of the literature is reported. Observations indicate that the public is generally aware of and attends to a growing body of health information resources, including traditional news media, advertising, and social networking. However, lay audiences often have no reliable way to assess the accuracy of health information found in the media, on the Internet, or in direct-to-consumer advertising. This inability to assess the information can lead to decision paralysis, with patients questioning what is known, what is knowable, and what their physicians know. Many patients have specific expectations for the care they wish to receive and have little difficulty making those expectations known. However, there are hazards in assuming that patients’ expressed desires are direct reflections of their underlying wants or needs. In trying to reconcile patients’ wants and needs for information about prescription medicines, a combination of policy and clinical initiatives may offer greater promise than either approach alone. CONCLUSIONS: Patients are bombarded by information about medicines. The problem is not a lack of information; rather, it is knowing what information to trust. Making sure patients get the medications they need and are prepared to take them safely requires a combination of policy and clinical interventions.